RIZIK – a risk management survey for Croatian museums geared towards the better assessment, prevention and reduction of risk (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of the survey on risk management in Croatian museums was to collect comprehensive data on the preparedness of Croatian cultural organisations for various risks in order to better assess, prevent and reduce risks.Approach and methodology. Against the background of the devastating damage caused by the March 2020 earthquake to cultural heritage in Zagreb, Croatia, the International Institute for the Restoration of Historical and Artistic Works, IIC-Croatian Group, conducted a national survey under the name of RIZIK. The online survey included 73 questions divided into four categories: general information about the institution, the property including buildings and collections, followed by questions on finances and audience. Questions on safety and regular maintenance, work and business plans, essential emergency services in case of danger, possible hazards and risks affecting the buildings and the collection, along with questions on measures that can help prevent or minimise risks and damage to the collection, the building, staff, and visitors, are part of the survey.Findings. As many as 188 museums were invited to participate in the survey, more than 100 responded, although some answered the questions only partially. This paper shows a cross-section of the general situation in Croatian museums, addresses the problem of modernising exhibition and depository spaces, describes the idea behind the survey, and discusses its results and possibilities for enhancement.Originality/value. The RIZIK survey is the first risk management survey sent to all museum institutions in the Republic of Croatia. The collected data are an important first insight into the current state and standards in Croatian museums, galleries and collections. Based on the results obtained, the survey participants can identify areas where they can strengthen or change their work practices, organisation and further planning.
Keywords: cultural heritage; earthquake demage; long-term prevention; risk assesment survey